Assistive Technology for Distance Education in Metaverse-Based Environment: A Rapid Review - Damasceno, Adson; Soares, Pamella; Santos, Ismayle; Souza, Jerffeson; Oliveira, Francisco (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2023)
Metaverses offer immersive virtual realities with potential applications in distance education. Integrating metaverse with assistive technology enables educational advancements and inclusive participation. This paper aims to gather evidence on metaverses, assistive technologies, and distance education. We conducted a Rapid Review analyzing seven studies out of 145 initial bases. As preliminary results, Chemistry Lab was the main focus (42.5%), with evaluation research as the primary strategy (57.1%). The challenges included instrumentation, technical issues, complex systems, student performance, presence, and accessibility assessment. The findings may aid researchers and practitioners in designing inclusive educational experiences in the metaverse.